Comparative analysis of genetic diversity in Norway spruce (Picea abies) clonal seed orchards and seed stands - CIOCIRLAN, Elena; ȘOFLETEA, Neculae; MIHAI, Georgeta; TEODOSIU, Maria; CURTU, Alexandru Lucian (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2021)
Norway spruce, Picea abies (L.) Karst. is the most important conifer species in Romania and the most planted tree species in the Carpathian Mountains. Here we compare the genetic diversity of four Norway spruce clonal seed orchards and two seed stands located in the Eastern Carpathians. A set of highly polymorphic nuclear microsatellite markers was used. The analysis of genotypic identity of ramets for each Norway spruce clone in all seed orchards indicated that nearly all sampled ramets (97%) were genetically identical. The genetic diversity in seed orchards (He=0.700) was slightly smaller compared to the seed stands (He=0.718). Allelic richness was higher in seed stands (10.874), compared to clonal seed orchards (8.941). The Bayesian analysis indicated a genetic structure with two clusters, one corresponding to the clonal seed orchards and a second one consisting of the two seed stands. Our results provide valuable information for the management of Norway spruce seed orchards in Romania.